Articulating design decisions communicate with stakeholders, deliver the best user experience, and keep your sanity - Greever, Tom (O'Reilly Media, 2014)
"With this practical video, UX designers will learn the principles and actionable methods for talking about their ideas with executives, marketers, and others who have influence over a web or app project--with the goal of winning over these stakeholders and creating the best user experience. Every designer must justify their designs to non-designers, yet most lack the ability to explain themselves in a way that fosters agreement. This video will not only help UX designers articulate their ideas, but will also be valuable for non-designers who want to learn to work better with designers."--Resource description page.
Title from title screen (viewed July 22, 2015). - Date of publication taken from resource description page
Keywords: User-centered system design; Human-computer interaction -- Vocational guidance; Business communication; Conception participative (Conception de systèmes); Communication dans l'entreprise